Comparative study of intramuscular gold and methotrexate in a rheumatoid arthritis population from a socially deprived area. Issue 6 (1st June 2001) - Hamilton, J; McInnes, I B; Thomson, E A; Porter, D; Hunter, J A; Madhok, R; Capell, H A
Abstract : OBJECTIVE: To compare the risk-benefit ratio of intramuscular gold (gold sodium thiomalate (GST)) and methotrexate (MTX) in a population with rheumatoid arthritis (RA) from a deprived area. METHODS: Patients with active RA were randomly assigned to open treatment with GST or MTX. Clinical and laboratory assessment was performed at 0, 12, 24, and 48 weeks. Results were analysed on an intention to treat basis. RESULTS: 141 patients were recruited—72 were randomly allocated to GST and 69 to MTX. There were no statistically significant differences found in either the clinical or demographic variables at baseline. At 48 weeks 31 (43%) patients continued to receive GST and 43 (62%) MTX. The median MTX dose achieved was 10 mg. Gold caused significantly more withdrawals for toxicity (43% GST v 19% MTX, p=0.0026, log rank test). Both groups experienced a significant improvement in erythrocyte sedimentation rate, C reactive protein, Ritchie Articular Index, and pain score by 24 weeks (p<0.001, Friedman test). Although a trend towards an improved Health Assessment Questionnaire (HAQ) score and global wellbeing was seen in both groups, this did not reach statistical significance. No differences in efficacy were found when the two groups were compared (Mann-Whitney). CONCLUSION: GST and low dose MTX showed equivalent efficacy, but toxicity was more common in patients treated with GST. GST, although more toxic, remains a useful alternative for patients in whom MTX is contraindicated.